Information Retrieval: Textual Indexing Using an Oriented Object Database - Mohammed Erritali (Institute of Advanced Engineering and Science, 2016)
The growth in the volume of text data such as books and articles in libraries for centuries has imposed to establish effective mechanisms to locate them. Early techniques such as abstraction, indexing and the use of classification categories have marked the birth of a new field of research called